2022
DOI: 10.1038/s41598-022-08948-w
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid protects against implant-associated infection by reducing biofilm formation

Abstract: Perioperative administration of tranexamic acid (TXA) is thought to be related to decreased postoperative implant-associated infection rates; however, the relationship remains unclear. We explored the inhibitory effect of TXA on infection both in vitro and in vivo. We investigated biofilm formation after TXA administration through different detection methods, all of which showed that TXA reduces biofilm formation in vitro and was further proven to be associated with decreased protein and polysaccharide content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It has been hypothesized that TXA reduces surgical site infections by reducing surgical site bleeding and subsequent biofilm formation, which may be especially critical in implant-associated infections [ 20 ]. Central venous access devices can also serve as a nidus for biofilm formation and infection [ 21 ], which may play a role in patients with hematologic malignancy, given widespread use of central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that TXA reduces surgical site infections by reducing surgical site bleeding and subsequent biofilm formation, which may be especially critical in implant-associated infections [ 20 ]. Central venous access devices can also serve as a nidus for biofilm formation and infection [ 21 ], which may play a role in patients with hematologic malignancy, given widespread use of central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we decided to analyze the synergistic effect of 10 mg/ml TXA with these antibiotics against a large collection of clinical strains isolated from patients with musculoskeletal infection. We used a 10-mg/ml concentration for a number of reasons: first, because we had previously demonstrated that it had a direct antibacterial effect on planktonic cells and that its effect was not dose-dependent (Benjumea et al, 2022a ; Wang et al, 2022 ); second, because it has been shown that ≥20 mg/ml can cause cellular toxicity (to chondral cells, epithelial cells, and fibroblasts), with the result that wound healing capacity could be compromised at higher doses (Parker et al, 2018 ; Eikebrokk et al, 2019 ; Bolam et al, 2021 ); and, third, because 10 mg/ml is the most widely used concentration in clinical studies (Sun et al, 2017 ; Montroy et al, 2018 ; Masaryk et al, 2022 ; Bi et al, 2023 ). Our analysis showed an overall reduction in turbidity of 10.9% for S. aureus and 2.2% for S. epidermidis strains when treated with TXA alone.…”
Section: Discussionmentioning
confidence: 99%
“…We tested 10 mg/ml TXA (shown to be optimal) (Benjumea et al, 2022a , b ; Wang et al, 2022 ) following CLSI guidelines using a microtiter plate (Clinical and Laboratory Standards Institute, 2018 ). The wells of a 96-well plate were inoculated with 50 μl of a suspension of 10 7 cfu/ml of each microorganism in Müller-Hinton broth and treated with 50 μl of 20 mg/ml TXA (as the final dose in the well will be 10 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm, an organized colony of microorganisms, forms an extracellular polymeric matrix of substance and shows adhesion with the neighbouring living and non-living surfaces 15 . It facilitates microorganism interaction and protect tolerant cells from the change in living environment for a long period of time 16 . The biofilm matrix strengthen the tolerance to disinfectants by wrapping the underlying cells 17 , 18 and by restricting diffusion of disinfectants into the biofilm matrix 19 .…”
Section: Introductionmentioning
confidence: 99%